Impact of Intermediate Indicators on Attaining Cognitive Program Outcomes - Tanseer Ali, M.; Abdur Rahman, Md.; Mannan, Mohammad Abdul; Saniat Rahman Zishan, Md; Chisty, Nafiz Ahmed; Hossain, Chowdhury Akram (Journal of Engineering Education Transformations, 2025)
Globally, engineering education is revolutionizing through the Outcome Based Education (OBE) model. To achieve accreditation under the requirements of the Washington Accord, the Program Outcome attainment has become a focal point in the Engineering field. Attempts to introduce a new OBE-based curriculum in the Universities of Bangladesh have faced many challenges for teaching staff and students. One of the crucial tasks is to achieve the defined Program Outcomes (POs) through Course Outcomes (COs). In this paper, an intermediate relationship between POs and COs is proposed. A case study and analysis of the proposed Intermediate Indicator to attain Cognitive Domain Program Outcomes has been presented to verify the efficiency and effectiveness of the methodology. Results clearly demonstrate that the Intermediate Indicator is essential to attaining program outcomes through course outcomes.